Multidrug Resistant Typhoid Fever in Children: A Review - Rahman, AKMM; Ahmed, M; Begum, RS; Ghosh, AK; Hossain, MZ (Journal of Dhaka Medical College, 2010)
DOI: 10.3329/jdmc.v17i2.6595 J Dhaka Med Coll. 2008; 17(2) : 121-126